Caracterização agronômica e correlações fenotípicas de híbridos de tomateiro salada indeterminado - Silva , Synara (2022)
The tomato is one of the most economically, socially and nutritionally important vegetables. Within the production chain, the search is for uniform fruits, with low production costs and high yields. In the genetic breeding program, the cultivars evaluation stage is performed for the selection of materials adapted to the region where they are grown. Therefore, it allows the identification of promising materials for a given environment, which contributes to better plant development in the production system. Hence, the objective was to select tomato genotypes, indeterminate salad, with high productivity, fruit quality and greater adaptability to the growing conditions and also to evaluate the phenotypic correlations of interest among the variables evaluated. The experiment was conducted at the Center for Development and Technology Transfer - CDTT/UFLA, in the city of Ijaci-MG. The work was conducted using a split plot randomized block design, evaluating 23 tomato hybrids, with 4 repetitions and 7 plants per plot. Nine commercial cultivars and fourteen experimental hybrids were used. The analyses consisted of evaluations by rating scale and objective agronomic evaluations. The attributes analyzed by grades were: fruit set, disease resistance, plant height, precocity, vigor, fruit size, and fruit format. The agronomic evaluations consisted in: total and commercial productivity, refuse, boxes per thousand plants, number of fruits per plant, average fruit mass, classification of fruits by size, 3A, 2A and 1A, extra and special, percentage of big fruits, diameter, length and shape of the fruits. The data were submitted to variance analysis using the SISVAR software and the arithmetic means were compared using the Tukey test at a 5% probability rate. There were significant differences for almost all characters, except for the vigor score analysis that considered all the similar treatments. The materials that stood out in performance were: 3100, 3101, 3102, 3104, 3105, 3106, 3107, 3124, 3125, 3126, 3127 and 3144, six commercial hybrids and six under development. These materials showed high productivity, good fruit classification, with a large part of the production with large fruits, good plant health and tolerance to major diseases at a field level. Therefore, the highlighted experimental hybrids presented excellent performance in the growing conditions of the city of Lavras and region. The phenotypic correlations showed that the higher the total yield, the higher the commercial yield, and, consequently, a low number of fruits with defects. The increase in the number of fruits can allow the largest amount of small fruits. In addition, the greater the average mass, in turn, the greater the amount of fruits that fall into the larger size categories. In this way, it is desirable to select hybrids that are productive and that maintain the size of fruits with greater market acceptance and greater profit for producers. The other information obtained through this trial will be important tools in the selection of new superior genotypes to be launched in the regional and national market in the future.